Evolucion de los residuos de nuarimol en pimientos cultivados en invernadero - Barba, A.=700 1 Camara, M.A.; Navarro Garcia, S.; Molina, R.; Escribano, J.A.
(Es, En)
ilus.,5 ref.
Keywords: NUARIMOL; FUNGICIDAS; RESIDUOS; CHILI DULCE; ESPAÑA; PIMIENTO